THE INFLUENCE OF LEADERSHIP STYLE AND WORK ENVIRONMENT ON EMPLOYEE WORK LOYALTY - Budianto; Frans Sahputra Silitonga (PT. MITRA ANGKASA INFORMATIKA, 2025)
Employee's loyalty is the loyalty that someone gives to the company where he works. Leadership style is behavior norm that is used by a person when he tries to influence the behavior of others. Work environment is one of the considerations for employees to continue working for a company. This research uses descriptive quantitative research. Data analysis techniques using multiple linear regression analysis. The research location is xyz. The measurement scale used in the research questionnaire is Likert scale. Simultaneously there is a positive and significant influence between the leadership style variable and work environment on employee's loyalty at xyz. Partially, leadership style variable does not have a positive and significant effect on employee's loyalty at xyzg. Partially, work environment variables have a positive and significant effect on employee's loyalty at xyz. Keywords: Leadership Style, Work Environment, Employee Loyalty